Etnografia móvel : uma proposta metodológica para os estudos da mobilidade na comunicação - Henriques, Sandra Mara Garcia (2016)
This doctoral thesis proposes a new look for the observation of mobile devices and their influence in the communicational process. From the studies focused on Sociology of mobility (MAFFESOLI, 2001; SIMMEL, 1987; BAUMAN, 2008; MEYROWITZ, 2004; URRY, 2007; 2011) wrapped in the perception of concepts that seek to outline the possibilities of understanding movement nowadays and the nomadism enabled by the fluidity of the interaction spaces, we use as a basis the Mobility Paradigm (URRY, 2007; 2011) to highlight the importance of social connections related to the technological mobility and the development of the mobile devices as an influence on information sharing and the formation differentiated mobile social networks that unite the hybrid spaces to technology (LÉVY, 2007; GREEN, 2002; DE CERTEAU, 1994; LEFEBVRE, 2000; VIRILIO, 1993; CASTELLS, 1999; LEMOS, 2007), potentiating the interaction among individuals, causing an impact in the milieu. For the comprehension of this process, we suggest the creation of a methodology that follows the object in constant motion and that are important to show the aspects that involve the interactions between individuals and between individuals and the places studied through mobility. To do so, we propose a Mobile Ethnography (MARCUS, 2001; BÜSCHER ET AL., 2011; JIRÓN, 2011; BÜSCHER E URRY, 2009; MUSKAT, 2013), research procedure in which the researcher becomes part of the process, in a co-presence, moving along with the researched object or group, armed with observation techniques to understand how the movement is created. This ethnographic approach is not based on studies of a single place, but of a number of places at the same time, and we highlight in this work the study of hybrid spaces and of the communication mobility. In this perspective, we did not perform the analysis of an object of study, but we propose application and development of the mobile ethnographic approach in two groups developed from the technological mobility context, Instagramers POA and Zombie Walk POA. The observation starts in the flows of information published through images and hashtags made by the groups in the mobile social network Instagram.